Association Between Risk of Falls and Body Mass Index Among Elderly Diabetic Patients - Israa Saleh Al-Ardhi, Hussein Hadi Atiyah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: most the countries of the world in the twenty-first century are witnessing a rapid growth of their population of the elderly. Aging has serious consequences for health and bodily functions and loss of balance, which increases the risk of falling and the risk of disease. 424,000 people around the world die due to falls. To avoid falling and maintaining a position we require balance. In this regard, the body mass index is one factor that may have an impact on balance. Aims of the study: To identify the association between the risk for falls and body mass index among diabetic elderly patients Methodology: A correlation design was conducted to study the association between risk for falls and body mass index among elderly diabetic patients from 18 / December /2021 to 1 /March /2022. The type of the sample was a non-probability (Purposive) sample to ensure that the data obtained from the study is accurate. (107) elderly diabetic patients were the sample size of this study from the Diabetes Center. Results: (37.4%) of participants within the age group (60-64) years old. (49.5%) was a man, (50.5%) was a woman. Illiterate (33.6%), (64.5%) of the participants are married, (37.4%) are unemployed, (94.4%) are living with family and (59.8%) are live in Urban. (48.6%) of participants have a moderate risk for falls. A High percentage of the study sample (44.9%) was overweight. Conclusion: The study concluded that body mass index (BMI) has an effect on body balance among the elderly, where there is a significant relationship between the risk of falling and body mass index (the p-value of marital status was 0.002). Where it found that the risk of falling was high among the overweight with a percentage (13.1%) because a higher proportion of the elderly participants in the study were in this category. In the second place, underweight, and then obesity, they had a high risk of falling than normal weight. Recommendation: Conduct periodic check-ups for the elderly concerning weight and height to find out the appropriate BMI for each person. Conducting introductory courses or seminars on the subject of falls, risk factors and consequences for the elderly from the age of 60 and over in all centers for the elderly. Conducting educational programs on fall prevention in all centers visited by the elderly and the nursing elderly home. Concerning diabetes patients, monthly check-ups should be carried to control patients and to clarify the prevention of complications of the disease that directly affect the fall.